Auxins and Cytokinins in Plant Development 2018 - Petrasek, Jan; Hoyerova, Klara; Motyka, Vaclav; Hejatko, Jan; Dobrev, Petre; Kaminek, Miroslav; Vankova, Radomira (International journal of molecular sciences, 2019)
The international symposium "Auxins and Cytokinins in Plant Development" (ACPD), which is held every 4⁻5 years in Prague, Czech Republic, is a meeting of scientists interested in the elucidation of the action of two important plant hormones-auxins and cytokinins. It is organized by a group of researchers from the Laboratory of Hormonal Regulations in Plants at the Institute of Experimental Botany, the Czech Academy of Sciences. The symposia already have a long tradition, having started in 1972. Thanks to the central role of auxins and cytokinins in plant development, the ACPD 2018 symposium was again attended by numerous experts who presented their results in the opening, two plenary lectures, and six regular sessions, including two poster sessions. Due to the open character of the research community, which is traditionally very well displayed during the meeting, a lot of unpublished data were presented and discussed. In this report, we summarize the contributions in individual sessions that attracted our attention.
Keywords: plant development; životní prostředí; Environment; Plant Development; signální transdukce; regulátory růstu rostlin; kyseliny indoloctové; Signal Transduction; Cytokinins; auxin; cytokininy; biologický transport; Plant Growth Regulators; Indoleacetic Acids; cytokinin; plant hormone crosstalk; metabolické sítě a dráhy; vývoj rostlin; Metabolic Networks and Pathways; Biological Transport